2015
DOI: 10.1128/aem.00604-15
|View full text |Cite
|
Sign up to set email alerts
|

Photoautotrophic Polyhydroxybutyrate Granule Formation Is Regulated by Cyanobacterial Phasin PhaP in Synechocystis sp. Strain PCC 6803

Abstract: Cyanobacteria are photoautotrophic microorganisms which fix atmospheric carbon dioxide via the Calvin-Benson cycle to produce carbon backbones for primary metabolism. Fixed carbon can also be stored as intracellular glycogen, and in some cyanobacterial species like Synechocystis sp. strain PCC 6803, polyhydroxybutyrate (PHB) accumulates when major nutrients like phosphorus or nitrogen are absent. So far only three enzymes which participate in PHB metabolism have been identified in this organism, namely, PhaA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 59 publications
2
46
0
1
Order By: Relevance
“…PCC 6803, and archaeal phasins. Analysis of PhaP from Synechocystis revealed that it is similar to thylakoidassociated proteins from different algal species and to a protein from Arthrospira platensis that contains a Phasin_2 motif (12). Many phasins have been identified in Archaea, but to date, only that of H. mediterranei has been experimentally studied.…”
Section: Phasin Protein Familiesmentioning
confidence: 99%
See 3 more Smart Citations
“…PCC 6803, and archaeal phasins. Analysis of PhaP from Synechocystis revealed that it is similar to thylakoidassociated proteins from different algal species and to a protein from Arthrospira platensis that contains a Phasin_2 motif (12). Many phasins have been identified in Archaea, but to date, only that of H. mediterranei has been experimentally studied.…”
Section: Phasin Protein Familiesmentioning
confidence: 99%
“…Secondary-structure in silico predictions for phasins PhaP1 to PhaP4 from R. eutropha, PhaP1 from Ralstonia solanacearum, PhaP from Ralstonia metallidurans (17), PhaP Az (18), and PhaP Sp (12) revealed that these phasins have a high percentage (close to 90%) of amino acids in an ␣-helix conformation. This was found to be a general characteristic of phasins (18)(19)(20).…”
Section: Structural Aspects Of Phasinsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCC6803, PHAs synthesis occurs in the presence of light and starts with the condensation of two Acetyl-CoA molecules by PhaA (acetyl-CoA-acetyltransferase), generating Acetoacetyl-CoA, then reduced by PhaB [3-oxacyl-(acylcarrier-protein) reductase 2] to (R)-3-hydroxybutyryl-CoA. At this stage, a heterodimer complex composed of PhaE [poly (3-hydroxyalkanoate) synthase component] and PhaC [poly(3-hydroxyalkanoate) synthase] polymerizes the Hydroxybutyryl-CoA to Polyhydroxybutyrate [21]. Recently, the activity of the co-expressed PhaE and PhaC in a cell-free system was determined and the values obtained were comparable to those of PHA synthases belonging to class I [22].…”
Section: Introductionmentioning
confidence: 99%